Analisis Biplot Robust dengan Metode Minimum Covariance Determinant dalam Mendeskripsikan Provinsi Sumatera Selatan Berdasarkan Karakteristik Angkatan Kerja Menganggur Dari Aspek Gender - Oki Dwipurwani; Dian Cahyawati; Eka Susanti (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
This study describes the unemployed workforce from the gender aspect in each district in South Sumatra Province (Sumsel), using secondary data taken from the Central Statistics Agency (BPS) in 2020. This study was analyzed using the statistical data description method, namely Robust Biplot Analysis, to data that contains outliers. The results obtained are the Biplot Robust graphic display which can explain the diversity of the data by more than 70%. The districts of Muara Enim, Lahat, Musi Banyuasin, Ogan Ilir, Prabumulih, Lubuk Lingau, and Palembang have the characteristics of the male Open Unemployment Rate (TPT) and the female TPT which is higher than the average for other districts. The districts of North Musi Rawas, Palembang, and Lubuk Lingau have the characteristics of high educated male and female unemployment. The districts/cities of Ogan Komering Ulu, Ogan Komering Ilir, and Musi Rawas Utara need attention because they have a higher percentage of unemployment in the desperate category than other districts, both male and female.